1987
DOI: 10.1002/j.1460-2075.1987.tb02556.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional reconstitution of influenza virus envelopes.

Abstract: We have examined several procedures for the reconstitution of influenza virus envelopes, based on detergent removal from solubilized viral membranes. With octylglucoside, no functionally active virosomes are formed, irrespective of the rate of detergent removal: in the final preparation the viral spike proteins appear predominantly as rosettes. Protein incorporation in reconstituted vesicles is improved when a method based on reverse‐phase evaporation of octylglucoside‐solubilized viral membranes in an ether/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(110 citation statements)
references
References 46 publications
6
104
0
Order By: Relevance
“…17 The different virosome preparations with and without DODAC were incubated for 30 min at pH 4.5, 37°C. Following low pH incubation the virosome suspensions were neutralized and tested for fusion activity.…”
Section: Formation and Characterization Of Cationic Virosomesmentioning
confidence: 99%
See 3 more Smart Citations
“…17 The different virosome preparations with and without DODAC were incubated for 30 min at pH 4.5, 37°C. Following low pH incubation the virosome suspensions were neutralized and tested for fusion activity.…”
Section: Formation and Characterization Of Cationic Virosomesmentioning
confidence: 99%
“…Previous studies have shown that the membrane fusion mediated by reconstituted virosomes closely resembles that of the intact virus. 17,19,20 Cationic lipids were incorporated into virosomes to attach plasmid DNA to the lipid bilayer surface by electrostatic interaction. Exogenous lipids (up to 30 mol% EPC and/or DODAC) were successfully incorporated into the virosomal membrane without affecting the acidic pH-induced fusion properties with target membranes (Figure 1).…”
Section: Nmol) Were Mixed With Increasing Amounts Of Virosomes Contaimentioning
confidence: 99%
See 2 more Smart Citations
“…26 Virosomes are prepared from membrane-enveloped viruses, in particular influenza virus, by solubilization of the viral membrane with a suitable detergent, removal of the nucleocapsids by ultracentrifugation and reconstitution of the viral envelope through extraction of the detergent. [27][28][29] Vesicles reconstituted in this manner consist of the viral lipids and the viral glycoproteins HA and NA and resemble the native virus particles in size and morphology. Moreover, influenza virosomes bind to sialic acid residues on the cell membrane and fuse with artificial and cellular target membranes in a strictly pH-dependent manner.…”
Section: Introductionmentioning
confidence: 99%